看護学分野での統計改革を目指して - 長島 俊輔 (日本看護研究学会雑誌, 2018)
The Publication Manual of American Psychological Association (APA manual, 2009) indicates that all articles must report the effect sizes in the "Result" section of the study. However, few nursing research articles report the effect sizes as a study result. This study investigates whether nursing research articles in Japan report the effect sizes for results of statistical analyses. The subjects of this study were 186 articles published from 2012 to 2016 in "Journal of Japan Society of Nursing Research" I investigated whether articles using t-test in this journal reported the effect sizes of d-family (i.e., the effect size for t-test. For example, Cohen's d, Hedges' g, gadj, and Glass' Δ) as a result of analysis. A total of 25 articles performed the t-test for statistical analysis. However, none of these articles reported the effect size of d-family. Only one study reported the partial correlation ratio (η) as the effect size. This result suggests that Japanese nursing researchers do not recognize the importance of reporting effect sizes in their studies. To accurately discuss the results of nursing research, all researchers need to understand the properties of effect sizes and report them in articles. APA論文作成マニュアルでは，研究結果に効果量の記載を必須としている。しかし，実際には，効果量を詳細に記載している論文はいまだ少なく，特にd族効果量の報告はほとんどない。そこで，本論文ではAPA論文作成マニュアルを採用している日本看護研究学会雑誌を対象に，d族効果量（Cohen’s d，Hedges’ g，Glass’ Δ ，gadj，dD）の報告状況を調査した。2012年から2016年に掲載された論文のうち，t検定を用いた論文を調査対象とした。結果として，t検定を用いた25の論文のうち，d族効果量を報告した論文はなかった。日本看護研究学会の知名度も考慮にいれると，この結果は日本の看護学分野全体でも効果量に対する認知が低い可能性を示唆している。効果量による研究の考察は，看護学研究のさらなる発展に寄与するものであり，今後，看護学分野でも効果量の記載を重要視していく必要がある。